2023
DOI: 10.3390/foods12234226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transglutaminase Treatment on the Structure and Sensory Properties of Rice- or Soy-Based Hybrid Sausages

Mirian dos Santos,
Wanessa Oliveira Ribeiro,
Jamille de Sousa Monteiro
et al.

Abstract: Partial substitution of meat with non-protein sources in hybrid meat products generally leads to a decrease in texture attributes and, consequently, in sensory acceptance. In this study, we investigated the effects of transglutaminase (TG) at two concentrations (0.25% and 0.5%) on the physicochemical, textural, and sensory properties of hybrid sausages formulated with concentrated soy or rice proteins. TG caused a reduction in the heat treatment yield of hybrid sausages, particularly those made with rice prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…ACTIVA TG-K acts as texture enhancer by forming the ε-(γ-glutamyl) lysine crosslinking of myosin heavy chain during the setting of salted fish paste, thereby contributing to a firmer and more cohesive texture [47]. Similar to previous studies on the use of TGs for improving gel strength [13][14][15][16][17][18], we observed an increase in the gel strength of the developed fish paste cake prototype containing 0.3% and 0.5% ACTIVA TG-K. Even though ACTIVA TG-K improved gel strength at both 0.3% and 0.5% concentrations, considering the manufacturing cost of the fish paste cakes, the optimal ratio of ACTIVA TG-K addition was decided at 0.3%.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…ACTIVA TG-K acts as texture enhancer by forming the ε-(γ-glutamyl) lysine crosslinking of myosin heavy chain during the setting of salted fish paste, thereby contributing to a firmer and more cohesive texture [47]. Similar to previous studies on the use of TGs for improving gel strength [13][14][15][16][17][18], we observed an increase in the gel strength of the developed fish paste cake prototype containing 0.3% and 0.5% ACTIVA TG-K. Even though ACTIVA TG-K improved gel strength at both 0.3% and 0.5% concentrations, considering the manufacturing cost of the fish paste cakes, the optimal ratio of ACTIVA TG-K addition was decided at 0.3%.…”
Section: Discussionmentioning
confidence: 66%
“…Panelists generally rated the appearance, color, flavor, texture, and overall liking of these products at a moderate level [15,16]. Notably, Muoi et al [17] found that the addition of 0.7% TGs significantly enhanced the gel properties of fried fish cakes made from frozen snakehead fish surimi, while dos Santos et al [18] reported improved textural and sensory properties in soy-based hybrid sausages with the addition of 0.25% TGs. In this study, we aimed to enhance the storage characteristics of fish paste cake using high-temperature and high-pressure processing, while minimizing associated decreases in physical properties by incorporating edible TGs.…”
Section: Introductionmentioning
confidence: 99%